Morena Mohlomi le Badimo: reading decolonial articulations into the intellectual property law curriculum. (Journal of Decolonising Disciplines, 2021)
The Council on Higher Education (CHE) expresses itself cogently in affirming the validity of the calls to specifically decolonise the LLB curriculum. Public discourse and the CHE report present an emerging clarion call for the academy to critically engage the question of decolonisation of the curriculum. This paper proposes Transmodernity as a methodological endeavor towards engaging African epistemologies in an effort to find alternatives in teaching various intellectual property law concepts. To tease out the fundamental decolonial question of how the dismembered can be re-membered, the paper tests the theory of Mohlomism and its applicability to the intellectual property law curriculum. Mohlomi was a mentor to the king of the kingdom of Lesotho, Morena Moshoeshoe I. He would travel around Southern Africa teaching society about his philosophy of truthfulness, justice, peace, the love of man and for sane humanism.  Re-membering the Being of the proverbial “other”, reverses the effect of the prevailing legacy of epistemicide in the curriculum and may gradually lead to a transformed legal   pedagogy. The paper discerns decolonisation as a project that inter alia seeks to create a pluriversal intellectual community that embosoms the epistemic traditions of the global South.
Keywords: Decoloniality, Intellectual Property Law, Mohlomism, Badimo, Transmodernity.